Antibacterial Activity Of Combination Of n-Hexane Extract Of Buas-Buas Leaves (Premna serratifolia L.) And Sappan Wood (Caesalpinia sappan L.) - Rissa Febriyanto; Isnindar Isnindar; Sri Luliana (Poltekkes Kemenkes Surakarta, 2022)
Background: The plants used in this study were buas-buas leaves (Premna serratifolia L.) and sappan wood (Caesalpinia sappan L.). The people of West Kalimantan use the buas-buas leaves and sappan wood as traditional medicine, and, based on research, they have antibacterial activity. Staphylococcus aureus and Escherichia coli are bacteria that cause nosocomial infections and have developed resistance to many antibiotics. This research was conducted to determine the antibacterial activity of the combination of n-hexane extract of buas-buas leaves and sappan wood. Methods: The antibacterial activity test was carried out by the agar diffusion method using a paper disc with a diameter of 6 mm. The antibacterial activity of a combination of n-hexane extract of buas-buas leaves and sappan wood in a ratio of 1:1, 2:1, and 1:2 at concentrations of 125, 250, and 500 ppm. Results: In this study, the combination of n-hexane extract of buas-buas leaves and sappan wood with various concentrations, even with increasing concentrations, did not show any inhibition zones. The factors that are thought to affect the absence of the inhibition zone are the concentration of the extract, the content of secondary metabolites, the solubility of the extract, and the length of contact time Conclusion: The combination of n-hexane extract of buas-buas leaves and sappan wood did not have antibacterial activity against Staphylococcus aureus and Escherichia coli in all comparisons and concentrations. It is recommended to test the antibacterial activity with a higher concentration